Identification and characterization of lactic acid bacteria isolated from rainbow trout, Oncorhynchus mykiss (Walbaum), with inhibitory activity against Lactococcus garvieae - Pérez-Sánchez, T (Journal of fish diseases, 2011)
© 2011 Blackwell Publishing Ltd.